ANALISIS KINERJA LEMBAGA EKONOMI MASYARAKAT SEJAHTERA PADA PROGRAM GERAKAN NASIONAL KAKAO DI KABUPATEN KOLAKA UTARA - Rijal, Muhammad; Amir, Muhammad; Tawai, Adrian (REZ PUBLICA, 2019)
This study aims to study and analyze the performance of the Cocoa Community Economic Institution (LEM) in North Kolaka Regency. This study uses a qualitative research type with descriptive analysis method with data collection techniques using three ways namely: interviews and document studies.The results showed that the National Movement Program in North Kolaka District had been running according to the operational standards listed in the technical guidelines, including garden rejuvenation, rehabilitation of gardens, intensification of gardens, empowerment of officers and farmers, construction and operation of post-harvest management units, and development of a technology database system. cocoa cultivation. The performance of LEM Prosperous in the cocoa gernas in North Kolaka Regency in terms of productivity, responsibility and accountability has been going well. While from the dimensions of service quality and responsiveness, it has not yet run well in terms of human resources and funding/budget. This means that with the good performance of LEM Prosperous, the Gernas Cocoa program in Kolaka Utar can be realized, and vice versa. Therefore, to improve the performance of the Prosperous LEM, it is necessary to increase the resources of the Prosperous LEM both in terms of human resources and funding/budget.